2016
DOI: 10.1016/j.chaos.2016.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Cosmology in one dimension: A two-component model

Abstract: We investigate structure formation in a one dimensional model of a matterdominated universe using a quasi-newtonian formulation. In addition to dark matter, luminous matter is introduced to examine the potential bias in the distributions. We use multifractal analysis techniques to identify structures, including clusters and voids. Both dark matter and luminous matter exhibit fractal geometry as the universe evolves over a finite range. We present the results for the generalized dimensions computed on various s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Further, the expected slopes for long (P ∼ k) and short (P ∼ k −3 ) wavelengths are correctly recovered by the Dirac-Milne simulations. This power law behavior in the nonlinear regime suggests a self-similar matter distribution in each model, pointing to the existence of a robust fractal dimension [21,31].…”
Section: Simulation Resultsmentioning
confidence: 80%
“…Further, the expected slopes for long (P ∼ k) and short (P ∼ k −3 ) wavelengths are correctly recovered by the Dirac-Milne simulations. This power law behavior in the nonlinear regime suggests a self-similar matter distribution in each model, pointing to the existence of a robust fractal dimension [21,31].…”
Section: Simulation Resultsmentioning
confidence: 80%
“…More recent studies (see, for example, Miller & Rouet, 2010;Joyce & Sicard, 2011;Benhaiem et al, 2013) have shown that power spectrum of initial perturbations in 1D models leads to fractal and multifractal structures in a wide range of scales. Detailed review of the problem can be found in Shiozawa & Miller (2016). Onedimensional cosmological models seem to give correct qualitative understanding of many events in the gravitational collapse of three-dimensional universe, but some ambiguity still remains as to how to connect the properties of 1D and 3D models (Joyce & Sicard, 2011).…”
Section: Introductionmentioning
confidence: 99%